Influence of Carbon Nanotube Inclusion on the Fracture Toughness and Ballistic Resistance of Twaron/Epoxy Composite Panels. (2015) - Hanif, W.Y. Wan; Risby, M.S.; Noor, Mazlee Mohd.
Abstract: The objective of this study is to investigate the effect of multi walled carbon nanotube (MWCNT) inclusion on the fracture toughness and the ballistic resistance properties in terms of energy absorption. The determination of fracture toughness of the epoxy/MWCNT matrix was carried out by using a single edge notch bending (SENB) method according to the ASTM D5045-99. Four different weight percentage (wt %) of multi-walled carbon nanotubes (MWCNTs) contents were used, which were 0 wt.%, 0.1 wt.%, 0.55 wt.% and 1.0 wt.%. Epoxy binder and MWCNTs were mixed by using a mechanical stirrer for 10 minutes at 1500 rpm speed and was further sonicated for 30 minutes at 30 Hz amplitude in order to enhance the homogeneity of MWCNTs in the matrix. The compositepanel comprised of Twaron fabrics with epoxy resin filled with MWCNTs was fabricated using hand layup and vacuum bagging assist method. The Twaron/epoxy/MWCNT composite panels weresubjected toa ballistic test using 9 mm Full Metal Jacket bullet at different impacting velocities. From the SENB results, it can be reported that MWCNT inclusion up to 1.0% w.t content shows significantinfluence towards increment of fracture toughness value.MWCNT also improves the ballistic resistance capability of the composite panel where it was found that the impact energy absorption value was proportionally increasewith theepoxy/MWCNT matrix's fracture toughness properties.